ʿEn Yahav: A Copper Smelting Site in the ʿArava - Yekutieli, Yuval (Bulletin of ASOR, 2005)
The paper describes the first field season at a small copper-smelting site in the central ʿArava, which had operated in the Early Bronze Age IV (EB IV) and most probably in the Roman period as well. The fieldwork focused on three main projects: a surface survey, a multipurpose sampling, and an excavation of a small probe. An additional goal set for this season was the formulation of a methodological procedure of bringing the lab into the field-namely, performing onsite, on-time, XRF (X-ray fluorescence) analysis. In addition to describing the finds, the paper describes innovative field methods for investigating copper smelting sites and, based on the preliminary fieldwork, it offers a socioeconomic reconstruction of the central ʿArava and its bordering zones during the EB IV.